Fabrication and properties of polybutadiene rubber-interpenetrating cross-linking poly(propylene carbonate) network as gel polymer electrolytes for lithium-ion battery. Issue 65 (16th July 2015) - Huang, Xueyan; Huang, Jiayi; Wu, Jianfeng; Yu, Xiaoyuan; Gao, Qiongzhi; Luo, Ying; Hu, Hang
<x xml:space="preserve">Abstract</x> Novel polybutadiene rubber interpenetrating cross-linking poly(propylene carbonate) network has been synthesized as GPEs with excellent electrochemical performances for lithium-ion batteries.